Intention to use eLearning-based continuing professional development and its predictors among healthcare professionals in Amhara region referral hospitals, Ethiopia, 2023: using modified UTAUT-2 model - Jenberu Mekurianew Kelkay; Sisay Maru Wubante; Deje Sendek Anteneh; Mitiku Kassaw Takilo; Chernet Desalegn Gebeyehu; Temesgen Ayenew Alameraw; Kassahun Dessie Gashu (BMC Health Services Research)
Abstract Background Continuing Professional Development (CPD) is provided through in-service programs organized based on competency development and lifelong learning for healthcare professionals to stay fit with the required knowledge and skills. However, healthcare professionals’ financial constraints and tight schedules sending them away from the workplace for CPD training is a challenge. eLearning is becoming the best solution to overcome those barriers and create accessible, efficient, flexible, and convenient professional development. However, evidence is limited on health professionals’ intention to use eLearning-based CPD and its predictors. Hence this study aimed to assess healthcare professionals’ intention to use eLearning-based CPD and its predictors in Amhara region referral hospitals, in Ethiopia. Methods A cross-sectional study was conducted from March 28 to April 28, 2023. A total of 976 healthcare professionals participated in this study. Proportional allocation and simple random sampling were used to select participants for the study. UTAUT2 model was applied to develop a theoretical framework. A structured self-administered questionnaire was used and a 5% pretest was performed. Data were entered into Epi data 4.6 and exported to SPSS 26 for descriptive analysis. AMOS 23 SEM was also used to describe and assess the degree and significance of relationships between variables. Results About 51.8% (506/976) (95% CI: 48.7–55.0) of participants have the intention to use eLearning for CPD. Performance expectancy (β = 0.233, p-value < 0.01), effort expectancy (β = 0.082, p-value < 0.05), facilitating condition (β = 0.102, p-value < 0.05), hedonic motivation (β = 0.199, P-value < 0.001), habit (β = 0.473, P-value < 0.001), and computer literacy (β = 0.116, p-value < 0.001) had a positive relationship with intention to use eLearning based CPD. Age and gender were also a moderator of the habit of using eLearning based on CPD. Conclusion and recommendation. Overall, healthcare professionals' intention to use eLearning-based CPD was found low. Performance expectancy, effort expectancy, facilitating condition, hedonic motivation, habit, and computer literacy had a significantly positive influence on the intention to use eLearning-based CPD. The development of a user-friendly eLearning-based CPD development that meets user expectations can enhance the intention to use.